(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The development of toll road infrastructure is one of the national strategic programs to improve connectivity and encourage regional economic growth. However, the existence of toll roads also has a direct impact on small business actors who depend on old traffic flows. This study aims to analyze the impact of toll road construction on the sustainability of the Karya Restaurant business in Lima Puluh District, Batu Bara Regency. This study uses a qualitative descriptive approach, with data collection techniques in the form of in-depth interviews, observation, and documentation. The results of the study showed a significant decrease in the number of customers and business turnover after the diversion of vehicle flow to the toll road. However, business owners implemented adaptation strategies by strengthening local services and utilizing social media. These findings provide strategic recommendations for local governments in developing inclusive policies for affected MSMEs.